USING BOUNDARY SCAN IN DIGITAL SYSTEMS - Kaminskaya, Marina (International Journal of Computing, 2014)
Proposed fault control method in digital systems. He was developed with deductive simulation. Was proposed to use standard IEEE 1149.1 Boundary scan for control additional virtual outputs.